1931 Ark. Acts 705-06, § 4 - (:unkn) unknown (My University, 1931)
Act of Mar. 26, 1931, No. 225, § 4: Required the registration of machine guns to the Secretary of State.
Keywords: MACHINE GUN RESTRICTION